Literature Review: Hubungan dan Peranan Interleukin-6 (Il-6) pada Penderita COVID-19 - Cindrayani, Sulis; Sukmana, Dhika Juliana; Hadiatun, Nurul; Aini, Aini (JSN : Jurnal Sains Natural, 2023)
Coronavirus disease 2019 or better known as COVID-19 is an acute respiratory disease caused by Savere Acute Respiratory Syndrome-2 (SARS CoV-2). The purpose of this study was to determine the role and relationship of interleukin-6 (IL-6) in patients with COVID-19. The research method is a Systematic Literature Review (SLR) using electronic articles in English and Indonesian, the year the article was published starting from 2019 with a secondary research design with supporting data with the theme of the study taken, namely with the keywords: COVID-19, interleukin-6, cytokine storm in COVID-19 sufferers. In searching articles with the help of several databases. On average, the results of the 8 research articles used in this literature review show that there is a relationship and role for interleukin-6 (IL-6) in people with COVID-19. In conclusion, IL-6 has a role and relationship to sufferers of COVID-19